Modelling the information seeking and searching behaviour of users with impairments: are existing models applicable?. Issue 2 (20th October 2020) - Berget, Gerd; MacFarlane, Andrew; Pharo, Nils
Abstract : Purpose: A substantial number of models have been developed over the years, with the purpose of describing the information seeking and searching of people in various user groups and contexts. Several models have been frequently applied in user studies, but are rarely included in research on participants with impairments. Models are purposeful when developing theories. Consequently, it might be valuable to apply models when studying this user group, as well. The purpose of this study was to explore whether existing models are applicable in describing the online information seeking and searching of users with impairments, with an overall aim to increase the use of models in studies involving impairments. Design/methodology/approach: Six models were selected according to the following criteria: the model should address information seeking or searching, include the interaction between users and systems whilst incorporating assistive technology. Two user groups were selected from each of the categories: cognitive, sensory and motor impairments, namely dyslexia, autism, blindness, deafness, paralysation and Parkinson's. The models were then analysed based on known barriers reported for these cohorts. Findings: All the selected models had potential to be applied in user studies involving impairments. While three of the models had the highest potential to be used in the current form, the other three models were applicable either through minor revisions or by combining models. Originality/value: This study contributes with a new perspective on the use of models in information seeking and searching research on users with impairments.